2018
DOI: 10.1002/acm2.12358
|View full text |Cite
|
Sign up to set email alerts
|

Dose rate response of Digital Megavolt Imager detector for flattening filter‐free beams

Abstract: In this study we investigated the dose rate response characteristics of the Digital Megavolt Imager (DMI) detector, including panel saturation, linearity, and imager ghosting effects for flattening filter‐free (FFF) beams. The DMI detector dose rate response characteristics were measured as a function of dose rate on a Varian TrueBeam machine. Images were acquired at dose rates ranging from 400 to 1400 MU/min for 6XFFF and 400 to 2400 MU/min for 10XFFF. Line profiles and central portal doses derived from the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Xu et al. found that the gamma passing rate decreased from 99.9% to 91.5% when the dose rate was increased from 400 to 1200 MU/min for 10X FFF beams on a DMI imager . While decreasing the dose rate may improve the PD analysis, it is not recommended since ASTRO guidelines state that “same files to be used for the patient delivery should be used for the QA measurements.”…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al. found that the gamma passing rate decreased from 99.9% to 91.5% when the dose rate was increased from 400 to 1200 MU/min for 10X FFF beams on a DMI imager . While decreasing the dose rate may improve the PD analysis, it is not recommended since ASTRO guidelines state that “same files to be used for the patient delivery should be used for the QA measurements.”…”
Section: Discussionmentioning
confidence: 99%
“…33 Xu et al found that the detector panel has a saturation in case of high dose-rate beams, but it was clinically insignificant even at the maximum dose rate of 2400 MU/min. 34 Pardo et al and Miri et al investigated FFF beam dosimetry plans and found no clinically relevant deviations, but in these studies plans were not included using beams over ca. 1000 MU.…”
Section: Discussionmentioning
confidence: 99%
“…found that the detector panel has a saturation in case of high dose-rate beams, but it was clinically insignificant even at the maximum dose rate of 2400 MU/min. 34 Pardo et al . and Miri et al .…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al investigated the dose rate response characteristics of the Digital Megavolt Imager (DMI) detector for flattening filterfree (FFF) beams (19) . They measured as a function of dose rate on a Varian TrueBeam machine.…”
Section: Gul and Inanmentioning
confidence: 99%